Penggunaan Ragam Bahasa Sarkasme pada Kolom Komentar Akun Tiktok @Vadelbadjideh - Nur Fadilah; Ari Nugrahani (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to describe the types of sarcasm found in the comment section of the TikTok account @vadelbadjideh, the types of posts that receive the most sarcastic comments, and the illocutionary speech acts contained in those comments. The research method used is descriptive qualitative, employing documentation techniques by capturing screenshots of comments from the most viewed video posts. The data were analyzed using a pragmatic approach based on Charles Morris’s theory and classified according to Elizabeth Camp’s sarcasm types and Searle’s speech act categories. The results show that lexical sarcasm is the most commonly used form by netizens, followed by propositional sarcasm, sarcasm with the word